Canadian public health experiences during COVID-19: a new framework for assessing evidence - Cotton, Christopher S.; LaBarge, Monica C.; Nordstrom, Ardyn (Frontiers in Public Health, 2025)
BackgroundPublic health emergencies like COVID-19 require public policy and practice decisions at a time of uncertainty and rapidly changing science.MethodsWe conducted qualitative, phenomenological interviews with 25 senior Canadian public health leaders at local, provincial, and federal levels. Interviews explored how evidence was assessed, interpreted, and utilized during Canada’s COVID-19 pandemic response. Data analysis followed rigorous inductive coding to identify key themes.ResultsParticipants highlighted limitations in traditional evidence hierarchies, emphasizing instead the critical role of timely, context-specific information such as predictive modeling, local surveillance data, and stakeholder insights. Officials described dynamically balancing methodological rigor with evidence credibility and applicability. We propose the Methodology-Credibility-Applicability (MCA) Evidence Framework, emphasizing simultaneous assessment across these three dimensions.DiscussionWe document the experiences of public health leaders during the COVID-19 crisis, focusing on the assessment and use of evidence in decision making. The results challenge established hierarchies for assessing evidence and highlight the need for flexible, multidimensional frameworks for evaluating evidence during crises.